Digital Micro Visualization Of Movements Through Motion Capture: A Case Study Of Joget Serampang Laut - Mohd Herrow, Mohd Firdaus; Azraai, Nurzaidi (Idealogy Journal, 2023)
Motion capture technology also known as MoCap is one the important and leading technology in the process of capturing, recording and digitizing a significant movement. It gives a high accuracy of movement information, high degree freedom in movement and high flexibility in the captured physical movement. A wide range of research uses motion capture technology to gather data and to create a new finding in sport, medical and military purposes to improve human activities. Recently, in the area of performing arts, a number of research has used this technology, especially to capture the movement of traditional dance and traditional martial art as a platform of perseveration, documentation, archiving and interactive learning material purposes. This paper was executed using a mix of qualitative and quantitative methodology. Interviews and literature reviews were used to expose the rich diversity of three elements: Joget Serampang Laut, art biomechanics and motion capture technology. On the other hand, 21 joint of art biomechanics and 42 set of optical tracking passive markers were placed on the dancer to record the dance routine of Joget Serampang Laut in a motion capture laboratory that used eight (8) unit Osprey digital motion capture camera. Cortex Analysis software was used as a form of data analysis instrument. The findings of the research included motion capture technology as an effective tool for synthesizing time-based trajectory information into single frame, time-independent images that contained useful information about movements and gestures. Micro visual images can be essential as a metaphor for human experience since it provides objective representation that informs human perception and stimulates interpretations. At the end of the research, micro visual can be a communicative content related to bodyline that contains implicit meaning. The gestural representation may be understood in a experiential or cultural denotation and connotation that can holistically benefit and enhance the cultural values. KEYWORDS: Motion Capture, Digital Micro Visualization, Joget Serampang Laut, Art Biomechanics